Heavy Metal Distribution in Soil Profiles in Riyadh (Saudi Arabia) - Al-Shayeb, S.M.; Seaward, M.R.D. (Asian Journal of Chemistry, 2010)
The distribution of Pb, Zn, Cu, Cr and Ni in Riyadh soil profiles was detennined. Their levels were investigated in relation to organic matter content, soil pH and samples location. Samples were collected from urban, suburban, rural, highway and industrial area. Surface soils of highway and urban areas were found to be highly polluted with Pb and with a lesser extent Zn. High correlation was found between Pb, Zn, Cu and Cr indicating automobiles as a common source. No evidence of Ni contamination of soils was obtained. Soil profile results showed that Pb, Zn and Cu were largely concentrated in the upper surface soils, which is attributed to the low rainfall in the study area. It was foulld that approximately 74.7% of the lead, '56.6% of the zinc and 40.3% of the copper are concentrated in the top 5 cm confirming an airborne origin.